ANALISIS PENDUKUNG KEPUTUSAN PENILAIAN PRESTASI KERJA BERDASARKAN SASARAN KERJA DAN PERILAKU KERJA TENAGA KEPENDIDIKAN - Maulita Lutfiani; Mohamad Syamsul Maarif; Trioso Purnawarman (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
This study aimed to 1) Analyze the implementation of employee performance target (SKP) on the assessment of the performance appraisal of educational personnel in the the Faculty of Veterinary Medicine, Bogor Agricultural University (FKH-IPB). 2) Analyze the application of work behavior to the assessment of the performance appraisal of educational personnel in FKH-IPB. 3) Formulate strategic recommendations to be made by the FKH-IPB to improve assessment of performance appraisal and work productivity of educational personnel. The scope of this research is the assessment of the performance appraisal of education personnel, particularly regarding the application of the SKP and work behavior element as an civil servant (ASN) performance appraisal system. This study used the Analytical Hierarchy Process (AHP) method by distributing questionnaires and interviews to 12 experts. The results showed that 1) Creativity and innovation need to be added in the assessment of SKP in FKH-IPB to increase the productivity of education staff the weight of SKP becomes 65.4%. 2) Improved assessment of work behavior is very good by conducting guidance and supervision of education personnel periodically through the commitment and discipline of education staff. 3) The most influential performance improvement strategy is through education.